Proyeksi Hidrograf Banjir Berdasarkan Data Curah Hujan Dan Tutupan Lahan DAS Dayeuhkolot: Flood Hydrograph Projection Based On Rainfall And Land Cover Data In The Dayeuhkolot Watershed - Putra, Ronny Eka; Rohmat, Faizal Immaddudin Wira; Harlan, Dhermi; Fernando, Rangga; Uzhelia, Verryn Aisha; Afriyani, Sicilia; Wiliya, Wiliya (Media Ilmiah Teknik Sipil, 2026)
Flooding is a frequent hydrometeorological disaster in the Dayeuhkolot Watershed, a sub-watershed of the Citarum River Basin, caused by high rainfall intensity and land cover changes. This study aims to project flood hydrographs in the Dayeuhkolot Watershed based on satellite rainfall data and land cover changes up to the year 2100. Rainfall data were obtained from GSMaP for the period 2018–2022 and calibrated using the quantile mapping method to match observed rainfall characteristics, while river discharge data were collected from the AWLR monitoring station operated by PJT II. Land cover analysis was conducted using Sentinel-2 imagery for the period 2017–2021 and projected to the year 2100 using the Malaccha method. Rainfall–runoff modeling was performed using the HEC-HMS software with the Soil Conservation Service (SCS) Synthetic Unit Hydrograph method. Model performance was evaluated using Nash–Sutcliffe Efficiency (NSE) and Root Mean Square Error (RMSE). The results show that out of 12 flood events analyzed, six models met the performance criteria with NSE values greater than 0.36. Land cover projections to 2100 indicate minor changes in forest areas, leading to an increase in the Curve Number value from 76.90 to 77.00, which resulted in a 0.33% increase in peak flood discharge from 2021 to 2100. These findings demonstrate that land cover changes influence flood hydrograph characteristics and can serve as a basis for flood mitigation planning in the Dayeuhkolot Watershed.